PORTFOLIO SELECTION DOW JONES DAN MARKOWITZ DENGAN PEMILIHAN SAHAM BENJAMIN GRAHAM DAN APLIKASINYA DI BEI PERIODE 2018-2023 - Haniel Natanael; Edison (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2026)
In this study, the authors compare stock portfolios created using the Dow Jones and Markowitz methodologies, which rely on stock recommendations from Benjamin Graham. The aim is to examine whether portfolios following these methods can outperform Indonesia's main stock market indices, the Jakarta Composite Index (JCI) and IDX30, over the period 2018 to 2023. The stock selection process uses Graham's rule by targeting companies whose earnings-to-price ratio is twice the yield on AAA-rated bonds (in this study using the Bank Indonesia (BI) rate averaged over 5 years from 2018 to 2023) and whose debt is less than its book value. The Dow Jones portfolio consists of 30 equally weighted stocks selected from eligible issuers, and the Markowitz portfolio is constructed following the mean-variance approach and Lagrangian function to obtain 14 stocks. This study examines both portfolios using weekly returns, standard deviations, and Sharpe ratios and examines whether they outperform the Jakarta Composite Index and IDX30. It can be seen that both portfolios outperform the index in terms of risk-adjusted returns, which are 0.32% per week for the Dow Jones portfolio and 0.42% per week for the Markowitz portfolio compared to the IHSG of 0.07% per week and the IDX30 of -0.01% per week.